PRAKTIKWARIA DALAMMELAKUKAN VOLUNTARY COUNSELING AND TESTING (VCT) - Marsofely, Reka LagoraMarsofely Lagora (JURNAL MEDIA KESEHATAN, 2016)
Transgender is a group of people that has higher risk of sexuality infection diseasecomparing than other groups that have as high of sexuality disease infection (such as whoreand gay) because they have many sexual partners. The reason of doing such business is thatfor money. As a matter of fact, they have low income, temporary worker and low educated.The data shows that there is a decreasing of transsexual visiting to Voluntary Counseling andTesting clinic (VCT). Today, VCT is the most effective way in the case of preventing andserving HIV/AIDS infection especially to the groups that have a high risk of infection liketransgender. The objective of the research is to know the factors that make transgendervisiting to Voluntary Counseling and Testing in Rejang Lebong regency in 2014. Thisresearch uses quantitative research with cross section approach. There were 100 people ofsamples by using random sampling. The result of the study showed that the factors in whichmade transgender visiting Voluntary Counseling and Testing clinic was attitude variable withp 0.000 score. In this case, it’s important to improve transsexual’s knowledge and skill tochange the attitude so it can give a significant value to prevent the sexuality infection diseasesand HIV AIDS in Rejang Lebong regency.